2023
DOI: 10.1002/adtp.202300360
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Behavior of Systemically Administered Encapsulin Protein Nanocages and Implications for their use in Targeted Drug Delivery

Claire Rennie,
Caitlin Sives,
India Boyton
et al.

Abstract: Encapsulins, self‐assembling protein nanocages derived from prokaryotes, are promising nanoparticle‐based drug delivery systems (NDDS). However, the in vivo behavior and fate of encapsulins are poorly understood. In this study, we probe the interactions between the model encapsulin from Thermotoga maritima (TmEnc) and key biological barriers encountered by NDDS. Here, a purified TmEnc formulation that exhibited colloidal stability, storability, and blood compatibility was intravenously injected into BALB/c mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…[We note that a recent report shows no immunological cross-reactivity in BALB/c mice between encapsulins from T. maritima and Quasibacillus thermotolerans, in spite of the existence of approximately 22% sequence identity between these proteins. 30 These encapsulin cousins are quite different in size, the former being 24 nm in diameter (T = 1) and the latter 42 nm (T = 4), although we do not assume that this is the source of their immunological orthogonality. ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[We note that a recent report shows no immunological cross-reactivity in BALB/c mice between encapsulins from T. maritima and Quasibacillus thermotolerans, in spite of the existence of approximately 22% sequence identity between these proteins. 30 These encapsulin cousins are quite different in size, the former being 24 nm in diameter (T = 1) and the latter 42 nm (T = 4), although we do not assume that this is the source of their immunological orthogonality. ]…”
Section: Resultsmentioning
confidence: 99%
“…A recent report from Care and colleagues showed that a single administration of encapsulin particles from the bacterium Thermotoga maritima in BALB/c mice was benign, producing no signs of physical distress or increases in the serum levels of several proinflammatory cytokines. 30 The same T. maritima encapsulins were used to recombinantly display foreign protein domains such as the Matrix protein 2 ectodomain of influenza A virus 21 as a protomer loop insertion and a truncated form of the gp350 receptor-binding domain from Epstein−Barr virus as a linear extension from the protomer's C-terminus. 20 The former particle was administered to mice with Freund's adjuvant and the latter with the Sigma adjuvant system.…”
Section: Introductionmentioning
confidence: 99%
“…We have already discussed this problem partially: we presently know that, at least, Quasibacillus thermotolerans encapsulin-containing cells do not cause an immune response when implanted into mice [ 59 ] and rats [ 60 ]. In addition, an article was recently published evaluating in vivo behavior of Thermotoga maritima encapsulins administered intravenously into mice [ 61 ]. The work demonstrated that IV-injected Thermotoga maritima encapsulins exhibited an excellent safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…As a necessary consequence of adsorption theory, it can be speculated that the properties of the PC and their relative abundance are dynamically changing in nature. [161][162][163] Indeed, the adsorption of proteins on NPs is a competitive and constantly changing complex process. In order to better interpret the changing character, alteration theory is put forward.…”
Section: Alteration Theorymentioning
confidence: 99%